2019
DOI: 10.5194/esd-2019-56
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Winter hydrometeorological extreme events modulated by large scale atmospheric circulation in southern Ontario

Abstract: Abstract. Extreme events are widely studied across the world because of their major implications for many aspects of society and especially floods. These events are generally studied in term of precipitation or temperature extreme indices that are often not adapted for regions affected by floods caused by snowmelt. Rain on Snow index has been widely used but it neglects rain only events which are expected to be more frequent in the future. In this study we identified a new winter compound index and assessed ho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…As periodicity in climate records has been regularly observed at global to local scales from millennial to interannual levels (Prokoph and Patterson, 2004;Zhao et al, 2013;Nalley et al, 2016;Champagne et al, 2019Champagne et al, , 2020, the observed presence of cyclicity in Ottawa's instrumental weather record is to be expected. The strongest observed cyclical influence on Ottawa weather present across all measured weather variables at annual and seasonal scales, as well as for temperature and precipitation extreme events, is the 9-13-year SSC.…”
Section: Periodic Trends Highly Influenced By Regional Climate Cyclesmentioning
confidence: 91%
“…As periodicity in climate records has been regularly observed at global to local scales from millennial to interannual levels (Prokoph and Patterson, 2004;Zhao et al, 2013;Nalley et al, 2016;Champagne et al, 2019Champagne et al, , 2020, the observed presence of cyclicity in Ottawa's instrumental weather record is to be expected. The strongest observed cyclical influence on Ottawa weather present across all measured weather variables at annual and seasonal scales, as well as for temperature and precipitation extreme events, is the 9-13-year SSC.…”
Section: Periodic Trends Highly Influenced By Regional Climate Cyclesmentioning
confidence: 91%